Molecular dynamics investigation of compressive behaviour of carbon nanotubes (CNT) reinforced calcium silicate hydrate (C-S-H) with different Ca: Si ratios - E.R.K. Chandrathilaka; Shanaka Kristombu Baduge; Priyan Mendis; P.S.M. Thilakarathna (Results in Engineering)
Understanding the mechanical behaviour and failure mechanisms of nanomaterial-reinforced cementitious pastes at the nano/molecular level is crucial in modifying such material structures to capture the full potential of high-performance nanomaterials. This study investigated the compressive performance and failure behaviour of carbon nanotubes (CNT) reinforced calcium silicate hydrate (C-S-H) with varying Ca: Si ratios, CNT types (armchair and zigzag, single-walled CNT (SWCNT), and muti-walled CNT (MWCNT)), CNT sizes, CNT orientation and loading directions using Molecular Dynamics (MD) simulations. The Ca: Si ratio was varied between 1.0 and 1.5 to understand the effects of silicate chain structure on the compressive behaviour of C-S-H and CNT-reinforced C-S-H. Varying CNT orientations and loading directions were used to understand the anisotropic structure and behaviour of CNT-reinforced C-S-H. The compressive strength was observed to be reduced with the addition of CNT into the C-S-H. The failure of CNT-reinforced C-S-H was mainly caused by the buckling of silicate chains/ silicate chain segments in the C-S-H, while CNT buckling was observed before the composite reached its peak stress. The MWCNT-reinforced C-S-H had comparatively improved compressive performance against the correlated SWCNT-reinforced C-S-H and plain C-S-H. These results are useful in understanding the mechanical behaviour of CNT-reinforced C-S-H and further upscaling to be used in the micro and mesoscale material models. The multi-dimensional molecular analysis of the CNT-reinforced C-S-H would facilitate more accurate modelling of CNT-reinforced C-S-H at the mesoscale, considering the isotropic behaviour observed in this study.